SOSIALISASI MAKANAN HALAL PADA ANAK SEKOLAH DASAR DENGAN PENDEKATAN EDUKATIF DI AIS (AL-MUNAWWIRIY ISLAMIC SCHOOL) SUMBERSARI JEMBER - Masahid, Ardiyan Dwi; Belgis, Maria; Witono, Yuli; Nafi', Ahmad; Azkiyah, Lailatul; Meilina, Lita; Brihatsama; Wahyuni, Livia (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2025)
The majority of Indonesia's population is Muslim; therefore, halal food education should be instilled from an early age, particularly at the elementary school. The activity aimed to enhance students’ literacy and understanding of halal food through an educational approach implemented at Al-Munawwiriy Islamic School (AIS), Sumbersari, Jember. The activity was conducted by the Research Group (Keris E-Food) from University of Jember in collaboration with AIS. The program began with an introduction Elmarom Bread production process, continued with an assessment of students’ initial understanding, and concluded with interactive socialization sessions. Educational methods employed included visual media, group discussions, and direct observation of the halal food production process. The results indicated that this educational approach was highly effective in increasing students’ knowledge of the concepts of halal and thayyib, as well as in fostering a critical attitude in selecting food in accordance with Islamic principles. Furthermore, the program reinforced the role of schools as institutions for embedding Islamic values. Early halal education has proven to be a strategic effort in shaping a generation that is both aware of and committed to halal food consumption.